Crossover from weak-antilocalization transport to quantum magnetoresistance of Dirac states in quenched Fe0.01Bi2Te3 single crystals with large magnetoresistance and high Hall mobility. (14th January 2020) - Wang, Li-Min; Wang, Shuo-Hong; Shen, Dong; Yang, Tien-Wei; Chen, I-Nan
Abstract: Magnetotransport properties with a large positive magnetoresistance (MR) and a high carrier mobility for applications have been achieved and probed for quenched Fe0.01 Bi2 Te3 single crystals. Large positive MR of ∼470% with a Hall mobility of ∼44 000 cm 2 V −1 s −1 at 5 K and 6 T has been observed on a quenched Fe0.01 Bi2 Te3 sample, in which the electrical parameters can be tuned by the quenching temperature T q . The MR behaviors for the quenched samples show a crossover from a weak antilocalization-dominant MR to a linear and non-saturating MR at temperatures of T * ≈ 58−100 K, where the large MR at low temperatures possibly originates from the mechanism of topologically protected backscattering. On the contrary, the MR behaviors for the strain-released sample do not show such a distinct crossover, where only linear-like and non-saturating MR behaviors can be observed. Different electrical transports between the quenched and strain-released samples indicate that the band structure, as well as the surface Dirac electrons in Fe0.01 Bi2 Te3, can be modified by the lattice strain. Furthermore, it is found that the low-temperature magnetoconductivity can be well described by the weak-antilocalization transport formula, while the high-field linear-like MR at T > T * can be explained in terms of Abrikosov's quantum transport of Dirac-cone states in quenched Fe0.01 Bi2 Te3 single crystals.